Classification of West Indian gherkin seeds vigor by respiratory activity - Moadir de Sousa Leite; Tiago de Sousa Leite; Salvador Barros Torres; Caio César Pereira Leal; Rômulo Magno Oliveira de Freitas (Revista Ciência Agronômica)
ABSTRACT Seed companies increasingly need to obtain rapid and reliable results on seed quality. In this context, this study aimed at verifying the efficiency of CO2 measurement for classifying West Indian gherkin (Cucumis anguria L.) seed vigor, using three seed lots of cv. “Do Norte” and three of cv. “Nordestino”. In order to assess seed physiological quality, the following tests were performed: germination, seedling emergence, emergence speed index, shoot length, total dry matter, electrical conductivity and respiratory activity. The experimental design was completely randomized, with four replicates, and the means were compared by Tukey test at 5% probability level. Pearson’s simple correlation was performed between the traditional vigor tests and the respiratory activity. The results of the germination and vigor tests allowed the West Indian gherkin seed lots to be classified into different levels of physiological quality. CO2 measurement is a promising method to identify vigor differences among West Indian gherkin seed lots.